2009
DOI: 10.1016/j.bbrc.2009.07.058
|View full text |Cite
|
Sign up to set email alerts
|

Leucine-rich amelogenin peptide induces osteogenesis by activation of the Wnt pathway

Abstract: We previously showed that one of the amelogenin splicing isoforms, Leucine-rich Amelogenin Peptide (LRAP), induced osteogenic differentiation of mouse embryonic stem cells; however, the signaling pathway(s) activated by LRAP remained unknown. Here, we demonstrated that the canonical Wnt/β-catenin signaling is activated upon LRAP treatment, as evidenced by elevated β-catenin level and increased Wnt reporter gene activity. Furthermore, a specific Wnt inhibitor sFRP-1 completely blocks the LRAP-mediated Wnt signa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
57
1
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(63 citation statements)
references
References 29 publications
4
57
1
1
Order By: Relevance
“…In contrast to the four peaks found in the original fractionation [29], here we found that Fraction C contained just two peaks, one of 43 amino acids and the other one corresponding to 45 amino acids in length, which correspond to the previously reported TRAP species [28]. The LRAP portion of amelogenin has been shown to induce osteogenesis in vivo [49] and osteoblast maturation in vitro [50,51], but the effect of Fraction C, containing the TRAP portion, was unclear. In the current study, we provide evidence that primary human osteoblasts and osteoblast-like cells are sensitive to the Fraction C and that this active peptide increases osteoblast maturation.…”
Section: Discussioncontrasting
confidence: 67%
“…In contrast to the four peaks found in the original fractionation [29], here we found that Fraction C contained just two peaks, one of 43 amino acids and the other one corresponding to 45 amino acids in length, which correspond to the previously reported TRAP species [28]. The LRAP portion of amelogenin has been shown to induce osteogenesis in vivo [49] and osteoblast maturation in vitro [50,51], but the effect of Fraction C, containing the TRAP portion, was unclear. In the current study, we provide evidence that primary human osteoblasts and osteoblast-like cells are sensitive to the Fraction C and that this active peptide increases osteoblast maturation.…”
Section: Discussioncontrasting
confidence: 67%
“…Given that canonical Wnt/ ␤ -catenin signaling regulates tooth shape and root formation [Yamashiro et al, 2007;Liu et al, 2008;Nemoto et al, 2009], the significantly higher ␤ -catenin expression in Bell stage-infected molars as compared to Cap stage-infected molars likely mediates the improved tooth morphology and root formation. Furthermore, since amelogenins activate the canonical Wnt/ ␤ -catenin pathway [Matsuzawa et al, 2009;Warotayanont et al, 2009] and Wnt/ ␤ -catenin signaling regulates Dspp transcript expression [Yamashiro et al, 2007], the significantly higher Dspp expression in Bell stage-infected molars may be due, in part, to the significantly approximately 25-30% higher (p ! 0.001) Amelx and ␤ -catenin transcript expression.…”
Section: Discussionmentioning
confidence: 99%
“…However, amelogenin transcripts and proteins have also been found in odontoblasts, pulp cells and cementoblasts in developing teeth [Oida et al, 2002;Veis, 2003;Papagerakis et al, 2003Papagerakis et al, , 2005, as well as in tissues not related to odontogenesis (for example, brain cells, hematopoietic cells and chondrogenic/osteogenic cells) [for review, see Deutsch et al, 2006]. In vitro and in vivo studies have clearly demonstrated that amelogenins have signaling properties [Hoang et al, 2002;Veis, 2003;Tompkins et al, 2005Tompkins et al, , 2006Zeichner-David et al, 2006;Ye et al, 2006;Matsuzawa et al, 2009;Warotayanont et al, 2009].…”
Section: Discussionmentioning
confidence: 99%
“…Certain isoforms of amelogenin, the predominant protein product of ameloblasts, have been shown to have signaling capability [34]. Notably, several studies have shown amelogenin signaling is effected, in part, through canonical Wnt signaling mechanisms as evidenced by the ability of full-length amelogenin and an amelogenin-spliced isoform, leucine-rich amelogenin peptide (LRAP), to induce increased protein levels of β-catenin and stimulate Wnt reporter gene activity [35,36]. A subsequent study has revealed LRAP stimulation of bone marrow stem cells induced osteogenesis with activation of the Wnt signaling pathway observed [37].The expression of Wnt10b by these cells was detected and the osteogenic activity of LRAP was inhibited by application of sFRP1.…”
Section: Wnt In Tooth Developmentmentioning
confidence: 98%